2001
DOI: 10.1177/014920630102700607
|View full text |Cite
|
Sign up to set email alerts
|

Human resources and the resource based view of the firm

Abstract: The resource-based view (RBV) of the firm has influenced the field of strategic human resource management (SHRM) in a number of ways. This paper explores the impact of the RBV on the theoretical and empirical development of SHRM. It explores how the fields of strategy and SHRM are beginning to converge around a number of issues, and proposes a number of implications of this convergence. http://www.ilr.cornell.edu/cahrs This paper has not undergone formal review or approval of the faculty of the ILR School. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,118
0
82

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,765 publications
(1,234 citation statements)
references
References 76 publications
34
1,118
0
82
Order By: Relevance
“…According to Wright et al (2001), a firm's human resource was different from human resource practices. The former referred to human capital pool (i.e.…”
Section: Human Resource Practicementioning
confidence: 99%
“…According to Wright et al (2001), a firm's human resource was different from human resource practices. The former referred to human capital pool (i.e.…”
Section: Human Resource Practicementioning
confidence: 99%
“…Typically, empirical studies demonstrated human resource management affect to the development and exploitation of intellectual capital (Wright, Dunford & Snell, 2001), knowledge creation & product development (Collins & Smith, 2006) and organizational learning (Snell, Youndt & Wright, 1996). These factors in turn facilitate the innovation in business.…”
Section: Critical Successful Factors For Innovationmentioning
confidence: 99%
“…For example, Wright et al (2001) argue that HPWS affect firm performance in many different ways and give one example that ". .…”
Section: Communication and Participationmentioning
confidence: 99%